Dampak penggunaan gadget terhadap pola komunikasi dan keseimbangan sosial generasi alpha di era digital - Febriani, Nadia; Kurniawan, Ficky Adi (Journal of Smart Education and Learning, 2025)
The digital era has profoundly transformed communication and social interaction patterns, particularly among Generation Alpha (born 2010–2025), who have been exposed to gadgets since early childhood. This study aims to analyze both the positive and negative impacts of gadget use on communication skills, social interaction, and the balance between digital engagement and real-life experiences. Using a systematic literature review method, data were obtained from accredited journals and scholarly publications that discuss the influence of gadget use among Generation Alpha. The analysis employed thematic and comparative approaches to identify patterns, similarities, and gaps across previous studies. The findings indicate that gadgets offer significant educational and informational benefits, promoting global connectivity and cognitive development. However, excessive use has led to digital dependency, reduced empathy, and diminished face-to-face interactions, which threaten social balance. This study contributes conceptually by positioning technology as a dual agent, both a catalyst for social learning and a potential disruptor of emotional development. The results highlight the need for digital literacy programs, structured screen-time management, and strengthened interpersonal engagement as key strategies for maintaining social and emotional well-being among Generation Alpha.